2018
DOI: 10.1126/scisignal.aap8734
|View full text |Cite
|
Sign up to set email alerts
|

Pin1 mediates Aβ 42 -induced dendritic spine loss

Abstract: Early-stage Alzheimer’s disease is characterized by the loss of dendritic spines in the neocortex of the brain. This phenomenon precedes tau pathology, plaque formation, and neurodegeneration and likely contributes to synaptic loss, memory impairment, and behavioral changes in patients. Studies suggest that spine loss is induced by soluble, multimeric Aβ42, whose post-synaptic signaling activates the protein phosphatase calcineurin. We investigated how calcineurin causes spine pathology and found that the cis-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 55 publications
(107 reference statements)
1
17
0
Order By: Relevance
“…Interestingly, in our study, cyclosporine-a was predicted to be a potential anti-AD drug, when using both the iPSC-derived NP cells and neurons. This is in line with recent data from Stallings' group, showing that cyclosporine-a blocked dendritic spine loss in Aβ42-treated cells [53]. Furthermore, cyclosporine-a inhibited amyloid synthesis and improved amyloid induced neurotoxicity in neuroblastoma cells [54].…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, in our study, cyclosporine-a was predicted to be a potential anti-AD drug, when using both the iPSC-derived NP cells and neurons. This is in line with recent data from Stallings' group, showing that cyclosporine-a blocked dendritic spine loss in Aβ42-treated cells [53]. Furthermore, cyclosporine-a inhibited amyloid synthesis and improved amyloid induced neurotoxicity in neuroblastoma cells [54].…”
Section: Discussionsupporting
confidence: 91%
“…In addition to the MARK pathway, Aβ application and AD-associated mutant APP expression also lead to the activation of a CAMKK2-AMPK pathway, which phosphorylates tau at Ser262 and causes spine loss (Mairet-Coello and others 2013). Moreover, a decrease in the isomerase activity of Pin1 may also mediate Aβ-induced loss of dendritic spines (Stallings and others 2018). Given the importance of MARK, Pin1, and phosphorylation at the Ser262/Ser356 epitope; it is likely that HSP90 and HSP70 chaperone complexes (discussed above) are involved in modulating the synaptotoxicity of dendritic tau, perhaps allowing aberrant dendritic tau to escape selective proteasome degradation (Dickey and others 2007).…”
Section: Loss Of Axonal Polarity: Tau Redistribution To Somatodendritmentioning
confidence: 99%
“…We find that overexpression of Pin1 triggered a loss of functional synapses and a reduction in the diversity of the types of post-synaptic spines. Similarly, Stallings et al, 2018 in found a decrease in spine number when the TAT-WW domain protein was applied to neurons. These results are in line with our findings as we observe spine loss when we overexpressed dominant negative forms of Pin1 (including the WW domain, data not shown).…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, conflicting results are observed as to the role of Pin1 in the regulation of post-synaptic spines between the global KO (Antonelli et al, 2016) and the conditional KO (Stallings et al, 2018). For instance, the global Pin1 knockout mice show an increase in spine density (Antonelli et al, 2016) while a recent paper shows that deleting Pin1 from the adult hippocampus decreases it Stallings et al (2018). These discrepancies in results, led us to reevaluate the role for post-synaptic Pin1 in dendritic spine morphology.…”
Section: Pin1 Regulates Post-synaptic Spinesmentioning
confidence: 99%
See 1 more Smart Citation